2020
DOI: 10.1136/sextrans-2019-054316
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of genital ulcer disease in South Africa: has donovanosis been eliminated?

Abstract: ObjectivesWe used an in-house molecular assay for the detection of Klebsiella granulomatis in ulcer specimens collected over a 12-year surveillance period in order to determine whether a diagnosis of donovanosis could be ascribed to genital ulcer disease (GUD) of unknown aetiology in our setting.MethodsBetween 2007 and 2018, a total of 974 genital ulcer specimens with no previously identified sexually transmitted (STI) pathogens were selected from STI aetiological surveys conducted in all nine provinces of Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Lymphogranuloma venereum (LGV) caused by C. trachomatis biovars L1-L3, chancroid (Haemophilus ducreyi), and donovanosis (Klebsiella granulomatis) have become uncommon in the last decade. 14,35,36 First-line syndromic regimen for GUD should include medications to treat HSV and syphilis (Table 3). Acyclovir is the medication of choice for HSV while benzathine benzylpenicillin, also called benzathine penicillin G (BPG), is the cornerstone of syphilis treatment.…”
Section: Genital Ulcer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Lymphogranuloma venereum (LGV) caused by C. trachomatis biovars L1-L3, chancroid (Haemophilus ducreyi), and donovanosis (Klebsiella granulomatis) have become uncommon in the last decade. 14,35,36 First-line syndromic regimen for GUD should include medications to treat HSV and syphilis (Table 3). Acyclovir is the medication of choice for HSV while benzathine benzylpenicillin, also called benzathine penicillin G (BPG), is the cornerstone of syphilis treatment.…”
Section: Genital Ulcer Diseasementioning
confidence: 99%
“…Lymphogranuloma venereum (LGV) caused by C. trachomatis biovars L1–L3, chancroid ( Haemophilus ducreyi ), and donovanosis ( Klebsiella granulomatis ) have become uncommon in the last decade. 14 , 35 , 36 …”
Section: Clinical Management Of the Symptomatic Patientmentioning
confidence: 99%
“…4 Although granuloma inguinale (donovanosis) accounted for a significant proportion of genital ulceration seen in KwaZulu Natal province in the latter part of the 20th century, this condition has been virtually eliminated and has not been reported in recent years. 5 The Centre for HIV & STI at the National Institute for Communicable Diseases (NICD) has been conducting STI etiological surveillance since 2007 to revise and update national syndromic management guidelines in use at PHCs throughout the country. From 2019 to 2020, surveillance was conducted at 3 sentinel sites in 3 provinces: Gauteng, Western Cape, and KwaZulu Natal (KZN).…”
mentioning
confidence: 99%
“…11 Klebsiella granulomatis was not detected in this study, a finding similar to a previous study that was conducted among the South African population that also reported negative Klebsiella granulomatis in genital ulcer specimens. 39 The negative results are probably because of public recognition of Donovanosis as a health problem with control measures or as a result of the improvement of health services or living standards. 14 Haemophilus ducreyi was the third-highest ulcerating pathogen in this study.…”
Section: Discussionmentioning
confidence: 99%